Membentuk Pemimpin Masa Depan Melalui Pelatihan Pengelolaan Keuangan - Saragih, Susanti; Margaretha, Yolla; Kristine, Fanny; Margaretha, Meily; Nursalin, Kezia Kurniawati; Sherlywati, Sherlywati; Kuswoyo, Chandra (Penerbit Goodwood, 2025)
Purpose: This community service initiative aims to support educational institutions in fostering the social and emotional development of adolescents by promoting awareness of saving, enhancing understanding of personal finance concepts, and equipping adolescents with essential financial skills to navigate future financial challenges. Methodology: The methodology employed in this initiative involved simulations and role-playing activities structured as a training program. The training focuses on the